Current challenges of Germany's energy transition project and competing strategies of challengers and incumbents: The case of direct marketing of electricity from renewable energy sources. (January 2015) - Wassermann, Sandra; Reeg, Matthias; Nienhaus, Kristina
Abstract: Electricity generated by renewable energies (RES-E) already accounts for 25% of Germany's electricity supply. This has led to recent discussions for a better market integration of RES-E. The paper examines how competing actors and their ideas on market integration developed new services for direct marketing according to their respective origins and tried to shape the regulatory framework. The paper analyses this process and explains the current shape of the field of direct marketing. Medium-sized structured actors, who favoured RES-E integration via the conventional wholesale power markets, and who formed early close coalitions with RES-E power producers at the same time, have been most successful in terms of market shares. Moreover, they have been very successful for different reasons in building-up coalitions with governance units and influencing the field rules and routines. Based on those findings, the paper will conclude with some policy advices for the future adjustment of the current regulative frameworks. As long as there is no evidence of how RES-E can be integrated most effectively and efficiently, policies should maintain a competition between different direct marketing strategies to find out which strategies serve the best in terms of achieving a successful energy transition. Highlights: Innovation sociological analysis of the market integration of electricity from renewables in the German electricity markets. Direct marketing of RES-E seen as a new strategic action field in the German "Energiewende". Strategies of incumbent and challenger actors to shape the rules of the field. Suggestions for the future design of policy instruments for direct marketing of RES-E.